Research on victimization of people affected by family or sexual violence - Bardales Mendoza, Olga (2012)
This article aims to reflect and alert on the treatment and ethical considerations that have the victims of violence. These should be considered in scientific research when the domestic and sexual violence issue is analyzed.This article is based on personal experience as a researcher in family and sexual violence in several institutions, and on experience of the State in promoting and producing research and evaluating several external protocols that are reached to issue recommendations.We will reflect on the most relevant protocols and research which lead us to propose a transformation in the researcher´s role, tending to assume an ethical attitude towards the research participants.